AB0046 Prevalence of tuberculosis infection in rheumatoid arthritis patients treated by corticosteroid pulse therapy. (1st June 2001) - Girolamo, C Di; Ferrucci, MG; Pappone, N; Crisci, C
Abstract : Background: Several pathogens have been previously reported in rheumatoid arthritis (RA) patients treated by corticosteroid pulse therapy (CPT) 1–3 and we recently described a case of upper lobe cavitary tuberculosis in a patient with RA under CPT associated to methotrexate. 4 Objectives: In order to establish the prevalence of tuberculosis infection in RA patients undergoing CPT, we analysed medical charts of consecutive patients affected by these disease who underwent this regimen. Methods: All the records were from patients attending the clinic for at least 2 years since the CPT administration and were analysed in order to detect a clinical diagnosis of tuberculosis. Routine blood analysis and a Chest x-ray film was available for all the patients in the period established for the follow-up, even if asymptomatic. At present, 11 females (mean age 57.54 years, range 40–74) have been identified, who took 1 gr of Methyilprednisolone i.v. daily in a 3-day course of CPT. One of them was taking methotrexate, 3 cyclosporin and 4 the combination of cyclosporin and methotrexate; 3 patients was under no DMARD. CPT was already administered in 3 patients no more than once in the previous year. Results: Two patients revealed a tuberculosis infection, characterised by cavitary lung involvement and meningitis respectively; diagnosis was confirmed by standard methods for tuberculosis in both the patients. One patient affected by tuberculosis belonged to the treatment group CPT + methotrexate, while the other suspended methotrexate less than one year before the administration of CPT. Conclusion: This finding underlines the necessity of close monitoring for severe opportunistic infections in rheumatoid patients during treatment with CPT and MTX, but seem to suggest a more prominent role played by CPT with respect to other DMARDs. References: Weusten BLAM, Jacobs JWG, Bijlsma JWJ. Corticosteroid pulse therapy in active rheumatoid arthritis. Semin Arthritis 1993;23:183–92 Van Der Veen MJ, Bijlsma JWJ. The effect of methylprednisolone pulse therapy on methotrexate treatment of rheumatoid arthritis. Clin Rheumatol. 1993;12:500–5 Boerbooms AMT, Kerstens PJSM, van Loenhout JWA, Mulder J, van de Putte LBA. Infections during low-dose methotrexate treatment in Rheumatoid arthritis. Semin Arthritis Rheum. 1995;24:411–21 di Girolamo C, Pappone N, Melillo E, Rengo C, Giuliano F, Melillo G. Cavitary lung tuberculosis in a rheumatoid arthritis patient treated with low-dose methotrexate and steroid pulse therapy. Br J Rheumatol. 1998;37:1136–7